1998
DOI: 10.1037/0021-843x.107.4.602
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol on the marital interactions of aggressive and nonaggressive husbands and their wives.

Abstract: This study examined the marital interactions of 60 maritally aggressive and 75 nonaggressive men and their wives under a baseline condition, and then after the husband had received no alcohol, a placebo, or alcohol. These sessions were videotaped and coded with the Marital Interaction Coding System by coders who were unaware of group status and specific condition. Aggressive couples exhibited more negative behavior and higher levels of negative reciprocity in the baseline interaction than did nonaggressive cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
135
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 33 publications
(55 reference statements)
2
135
2
2
Order By: Relevance
“…In addition, several studies of marital behavior have demonstrated that alcohol administration to men increases the extent of negative verbal behavior displayed by the men and their partners (e.g. Jacob & Krahn 1988;Leonard & Roberts 1998).…”
Section: Alcohol and Intimate Partner Violence: When Can We Say That mentioning
confidence: 99%
“…In addition, several studies of marital behavior have demonstrated that alcohol administration to men increases the extent of negative verbal behavior displayed by the men and their partners (e.g. Jacob & Krahn 1988;Leonard & Roberts 1998).…”
Section: Alcohol and Intimate Partner Violence: When Can We Say That mentioning
confidence: 99%
“…Although some early alcohol and sexuality research found significant placebo effects (Abrams & Wilson, 1983;George & Marlatt, 1986), the majority of recent sexuality research has not (Abbey et al, 2000;Fromme, D'Amico, & Katz, 1999;MacDonald, Zanna, & Fong, 1996;Norris & Kerr, 1993). Aggression research also has not found significant placebo effects (Chermack & Giancola, 1997;Leonard & Roberts, 1998). …”
mentioning
confidence: 99%
“…During the same period, researchers from a variety of disciplines have repeatedly found that domestic violence is influenced by a much wider range of factors (Elliott, 1977;Rounsaville, 1978;Straus, 1973). Violence between intimates and family members stems from a complex of etiological processes with neurological (Dutton, 2001;Meloy, 1992;Schore, 2003a,b), psychological (Dutton, 2002;Dutton & Holtzworth-Munroe, 1997a,b;Dutton, Saunders, Starzomski, & Bartholomew, 1994;Dutton & Starzomski, 1993;Hamberger & Hastings, 1991;Holtzworth-Munroe, Bates, Smutzler, & Sandin, 1997;Holtzworth-Munroe, Stuart, & Hutchinson, 1997), interpersonal (Jacobson et al, 1994;Leonard & Roberts, 1998;Margolin, John, & Gleberman, 1989), situational (Eckhardt, Barbour, & Davis, 1998;Fagan, 1989;Fagan, Stewart, & Hansen, 1983), and cultural influences (Archer, 2005;Dutton, 1985). The etiology of intimate partner violence has been found to have long term development (Dutton, 2000(Dutton, , 2002 stemming from early family influences such as witnessed violence (Dutton, 2000;Egland, 1993), shaming (Dutton, Starzomski, & Ryan, 1996;Dutton, Swanson, van Ginkel, & Starzomski, in press), and trauma (Dutton & Holtzworth-Munroe, 1997a,b).…”
Section: Introductionmentioning
confidence: 99%